Development of a genetic risk score to predict the risk of hypertension in European adolescents from the HELENA study - Pérez-Gimeno, Gloria; Seral-Cortes, Miguel; Sabroso-Lasa, Sergio; Esteban, Luis Mariano; Lurbe, Empar; Béghin, Laurent; Gottrand, Frederic; Meirhaeghe, Aline; Muntaner, Manon; Kafatos, Anthony; Molnár, Dénes; Leclercq, Catherine; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: From genome wide association study (GWAS) a large number of single nucleotide polymorphisms (SNPs) have previously been associated with blood pressure (BP) levels. A combination of SNPs, forming a genetic risk score (GRS) could be considered as a useful genetic tool to identify individuals at risk of developing hypertension from early stages in life. Therefore, the aim of our study was to build a GRS being able to predict the genetic predisposition to hypertension (HTN) in European adolescents. Methods: Data were extracted from the Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA) cross-sectional study. A total of 869 adolescents (53 % female), aged 12.5-17.5, with complete genetic and BP information were included. The sample was divided into altered ( 130 mmHg for systolic and/or  80 mmHg for diastolic) or normal BP. Based on the literature, a total of 1.534 SNPs from 57 candidate genes related with BP were selected from the HELENA GWAS database. Results: From 1534 SNPs available, An initial screening of SNPs univariately associated with HTN (p < 0.10) was established, to finally obtain a number of 16 SNPs significantly associated with HTN (p < 0.05) in the multivariate model. The unweighted GRS (uGRS) and weighted GRS (wGRS) were estimated. To validate the GRSs, the area under the curve (AUC) was explored using ten-fold internal cross-validation for uGRS (0.802) and wGRS (0.777). Further covariates of interest were added to the analyses, obtaining a higher predictive ability (AUC values of uGRS: 0.879; wGRS: 0.881 for BMI z-score). Furthermore, the differences between AUCs obtained with and without the addition of covariates were statistically significant (p < 0.05). Conclusions: Both GRSs, the uGRS and wGRS, could be useful to evaluate the predisposition to hypertension in European adolescents.